Quality of Human Resource Practices and Employee Job Satisfaction - Bjarki Pétursson 1993- (2018)
The purpose of this study was to measure the quality of the HRDs and if there was a difference on employees‘ job satisfaction between companies depending on the quality of the HRDs within the companies. The quality of the HRDs was measured with a questionnaire and the employees‘ overall job satisfaction were complete results from the competitions “Private and Governmental company of the year 2017 and 2018“. Participants in this study were 56 companies in Iceland, 19 private and 37 governmental. All the companies had at least 50 employees. Representatives of the HRDs within the companies answered a questionnaire on behalf of the companies. The questionnaire, which was created by the author of this study and his mentor, was sent to all participants via e-mail on the 19th of March 2018. The response rate was 45.53%. Pearson‘s correlation and multiple regression was conducted on the data. The results indicated that quality of HRDs was not affective in terms of employees‘ overall job satisfaction so the main hypothesis failed. Some subcategories under the questionnaire correlated significantly with other subcategories under the overall job satisfaction. Further research are needed. Keywords: job satisfaction, human resources, human resource management, human resource quality, human resource department Tilgangur rannsóknarinnar var að mæla gæði mannauðssviðanna og ef munur væri á starfsánægju starfsmanna á milli fyrirtækja útfrá gæðum mannauðssviðanna í fyrirtækjunum. Gæði mannauðssviðanna voru mæld með spurningalista og starfsánægja starfsmanna voru tilbúnar niðurstöður frá fyrirliggjandi gögnum frá keppnunum “Fyrirtæki og Stofnun ársins árið 2017 og 2018”. Þátttakendur í þessari rannsókn voru 56 fyrirtæki á Íslandi, þar af 19 einkafyrirtæki og 37 ríkisstofnanir. Öll fyrirtækin höfðu að lágmarki 50 starfsmenn. Forsvarsmenn mannauðssviðs svöruðu spurningalista fyrir hönd fyrirtækjanna. Spurningalistinn, sem var búinn til af höfundi og leiðbeinanda rannsóknarinnar, var sendur á alla þátttakendur með e-maili þann 19. ...